2021
DOI: 10.33860/jik.v15i2.482
|View full text |Cite
|
Sign up to set email alerts
|

Uji Efikasi Kapsul Pare-Primakuin dan DHP-Primakuin serta Pengaruhnya terhadap Kualitas Hidup Pasien Malaria Falsiparum Tanpa Komplikasi di RSUD Manokwari Tahun 2019

Abstract: Penelitian ini bertujuan untuk menganalisis efek terapi kombinasi obat antimalaria terhadap kualitas hidup pasien malaria falsiparum. Penelitian ini merupakan penelitian eksperimental murni (true-experimental). Jumlah sampel sebanyak 134 pasien penderita malaria di RSUD manokwari. Variable penelitian meliputi karakteristik responden, suhu aksila, hemoglobin, Gametosit (/µL darah), gejala klinis responden, Jumlah Parasit Aseksual dan Gametosit, dan Kualitas Hidup SF-36. Analisis data yang digunakan adalah uji c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Artemisinin-combination therapy (ACT) and primaquine have been replaced with chloroquine, sulfadoxine-pyrimethamine, and quinine due to the growing number of cases of antimalarial drug resistance in the past ten years [15,46]. However, ACT and primaquine regimen was given based on the high efficacy of ACT and primaquine in some studies in Indonesia [47][48][49][50]. A study from West Papua, Indonesia, reported that using ACT at a dose of 0.25 mg/kg body weight could cure malaria patients due to P. vivax in an abbreviated time if the patient complied Review Article [51].…”
Section: Antimalarial Regimen In Indonesia and Its Emerging Resistanc...mentioning
confidence: 99%
“…Artemisinin-combination therapy (ACT) and primaquine have been replaced with chloroquine, sulfadoxine-pyrimethamine, and quinine due to the growing number of cases of antimalarial drug resistance in the past ten years [15,46]. However, ACT and primaquine regimen was given based on the high efficacy of ACT and primaquine in some studies in Indonesia [47][48][49][50]. A study from West Papua, Indonesia, reported that using ACT at a dose of 0.25 mg/kg body weight could cure malaria patients due to P. vivax in an abbreviated time if the patient complied Review Article [51].…”
Section: Antimalarial Regimen In Indonesia and Its Emerging Resistanc...mentioning
confidence: 99%